Penerapan Asas Itikad Baik dan Kepastian Hukum dalam Sengketa Penolakan Klaim Asuransi Jiwa Syariah: Analisis Putusan Pengadilan Agama Medan Nomor 198/Pdt.G/2025/PA.Mdn - Imamah, Mutia Izzatun Nurul; Muallifin, Darin Arif (Institut Agama Islam Sultan Muhammad Syafiuddin Sambas, 2026)
This research examines the application of good faith and legal certainty principles in resolving Islamic economic disputes at the Medan Religious Court through analysis of verdict Number 198/Pdt.G/2025/PA.Mdn concerning rejection of sharia life insurance claims by PT Prudential Sharia Life Assurance against beneficiary heirs. Employing normative juridical methodology with case and conceptual approaches, this study analyzes the integration of positive law with Islamic legal principles in judicial considerations. Research findings indicate that the Panel of Judges applied the good faith principle (husn al-niyyah) in evaluating insurer conduct that rejected claims based on administrative grounds after policy issuance, constituting breach of contract. Legal certainty principle implementation manifested through judicial affirmation that claim settlement delays exceeding Financial Services Authority regulatory standards violated consumer protection rights. Judicial reasoning demonstrated progressive synthesis between Article 1338 Civil Code, Article 36 Compilation of Sharia Economic Law, and pacta sunt servanda principle in Islamic jurisprudence. This verdict strengthens consumer protection mechanisms and provides judicial precedent encouraging transparency enhancement and accountability in sharia insurance industry practices, thereby contributing to jurisprudential development of Islamic economic law in Indonesia.